SUCCESSFUL TREATMENT OF MASSIVE PULMONARY EMBOLISM WITH CARDIOGENIC SHOCK AS A FIRST MANIFESTATION OF COVID-19 INFECTION - Mitevska I; Grueva E; Kandic E; Bosevski M (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University Skopje, R.N.Macedonia, 2021)
COVID-19 infected patients have increased the risk for thromboembolic complications which can cause many organ dysfunctions that leads to premature patient’s mortality (1). Our patient was admitted because of sudden chest pain and shortness of breath. In order to establish the cause of hemodynamic instability urgent bed site echocardiography was performed with showed indirect signs of pulmonary embolism with right ventricular dysfunction. Pulmonary CT angiography showed the presence of massive pulmonary embolism (PE) which was complicated by right ventricular dysfunction and hemodynamic instability. The patient was successfully treat- ed with fibrinolysis. The PCR analysis was positive for COVID-19. This is case of pulmonary embolism complicated with cardiogenic shock as a first manifestation of COVID-19 – infection at our clinic since the start of the pandemic.